Synchronised Range Queries in Distributed Simulations of Multi-agent Systems - Suryanarayanan, V; Craenen, B G W; Theodoropoulos, G K (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
Range-Query is an important associative form of data access in distributed simulations and Distributed Virtual Environments. This paper discusses the problem of Range-Queries in the context of distributed simulation of multi-agent systems. An algorithm is presented for performing instantaneous Queries within an optimistic synchronisation framework and in the presence of dynamic migration of the simulation state. A quantitative evaluation of the effectiveness of the algorithm under different conditions is also presented.